Symposium 8: Flourish: the ecpd project: Symposium Introduction - Chesney, Sarah; Howard, James (Proceedings of the International Conference on Networked Learning, 2008)
This symposium focuses on the conference themes of Embedding Networked Learning in Institutions and Networked Lifelong Learning. This symposium will discuss the rationale, aims, methodological approach and user experience underpinning Flourish: the eCPD project, a Joint Information Systems Committee (JISC) funded study under the Users and Innovations programme. Flourish aims to give staff in a newly created university the opportunity to engage with an eportfolio first hand for their own continuing professional development. This study of staff approaches and attitudes to using an eportfolio is judicious, with the national driver for personal learning spaces (DfES 2005), the growth in eportfolio use throughout the educational sector and society’s current fascination with user created online content as embodied in the Web 2.0 phenomena. The symposium presenters represent a 360° perspective of Flourish and will include presentations from: The Educational Developer The Software Developer The Staff User The first paper will give an overview of the Flourish project, which is managed by the Centre for the Development of Learning and Teaching at the University of Cumbria. The paper will discuss how the project team aims to embed a staff eportfolio within existing working practices and CPD processes. It will evaluate one specific approach to overcoming the challenges encountered when introducing staff to new technologies, against the backdrop of competing pressures and time demands in a newly formed, geographically dispersed university. Building on the first paper, the second paper focuses on the development and enhancement of educational software and how the e-portfolio chosen by the Flourish team (in this case PebblePad) has been adapted to suit the needs of professional teaching, learning and research staff. The third paper offers the audience a view of the project and the use of an eportfolio from the perspective of a member of staff at the University of Cumbria. This member of staff started using the eportfolio whilst studying for the compulsory to new staff Post Graduate Certificate in Learning and Teaching in Higher Education. This paper discusses the experience of a non traditional learner against the background of the current UK national agendas including Widening Participation.